»Y’a que les très très vieux/ Qui ont encore l’espoir de mourir de vieillesse«. Alter und Apokalypse im französischen Chanson seit der Mitte des 20. Jahrhunderts [La vieillesse et l'apocalypse dans la chanson française depuis le milieu du XXe siècle] - Dietmar, Rieger (KulturPoetik, 2015)
After an introduction to the genre »chanson« and its fascination with real life, this article investigates the different ways in which French (and Franco-Canadian) chansons deal with ageing and old age. The study looks at the songs’ lyrics, which describe or represent old age in a manner between stereotype and intimate confession, and at the authentic or inauthentic performance of the chanson by its singer or singer-songwriter. The analyses are followed by an overview of chansons describing the end of the world. It can be shown that many of these songs focus on the feelings of lovers facing the apocalypse and that in more than one case chansons envisioning the last moments of the world contain a mixture of fear and parody.